Obedience and Servant Leadership Apollis, Appies, Buti, Buys - Baron, Eugene; Botha, Nico Adam (UJ Press, 2020)
In celebrating a quarter of a century of the Uniting Reformed Church in Southern Africa (URSCA) (1994 2019), quite a few well-organised activities and events took place. These activities reflect a mix of serious academic seminars and liturgical celebrations of which the ones in the Cape, both in Belhar and at the University of the Western Cape (UWC) warrant special mention. In his sermon based on John 17 at the closing liturgical celebration at UWC, Prof Daan Cloete raised several pertinent issues pertaining to unity and justice as a challenge to the leadership of URCSA. Despite all the significant events taking place throughout the year (2019), there has been a major deficit. Attempts at serious historiography are few and far between. This book is an attempt at starting such a study process. However, to put it modestly to contribute to the writing of the history of the URCSA. It has been resolved to start right at the beginning: the founding synod of URCSA with a specific focus on the constituting moderature. The book discusses the issues that were looming large at the founding Synod in 1994 which captures the 'miracle' and the euphoria that emerged amidst some delicate matters and issues that would have posed some serious impediments that would have jeopardise the unification before it even started. In calling into service the pastoral or praxis cycle the contributions of the first moderature of URCSA: Rev Nick Apollis (moderator), Rev Leonardo Appies (Scriba Synodii) Rev Dr Sam Buti (Assessor) and Rev JD Buys (Actuaris), of the 1994 General Synod elections are presented in this book. The authors were interested in answering the question: In what way did the moderature members of URCSA assist in the transformation of church and society? The book showcases, how not only systems and structures are essential in transformation processes, but people - who take up the task in obedience and servitude.